2013
DOI: 10.1016/j.cell.2013.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Sperm, but Not Oocyte, DNA Methylome Is Inherited by Zebrafish Early Embryos

Abstract: SUMMARY 5-methylcytosine is a major epigenetic modification that is sometimes called “the fifth nucleotide.” However, our knowledge of how offspring inherit the DNA methylome from parents is limited. We generated nine single-base resolution DNA methylomes, including zebrafish gametes and early embryos. The oocyte methylome is significantly hypomethylated compared to sperm. Strikingly, the paternal DNA methylation pattern is maintained throughout early embryogenesis. The maternal DNA methylation pattern is main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
415
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(452 citation statements)
references
References 48 publications
32
415
0
5
Order By: Relevance
“…The epigenetic states of sperm and oocytes are highly asymmetric in mice (Cedar and Bergman 2012) and zebrafish (Mhanni and McGowan 2004). Recently, two independent studies of zebrafish genome-wide DNA methylation profiles revealed that the paternal methylomes are stably inherited without significant changes from fertilization into the sphere stage; by contrast, maternal methylomes are reprogrammed such that their epigenetic states match the paternal methylomes after fertilization (Potok et al 2013;Jiang et al 2013). These findings suggest that the paternal DNA and maternal DNA undergo different dynamic changes.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The epigenetic states of sperm and oocytes are highly asymmetric in mice (Cedar and Bergman 2012) and zebrafish (Mhanni and McGowan 2004). Recently, two independent studies of zebrafish genome-wide DNA methylation profiles revealed that the paternal methylomes are stably inherited without significant changes from fertilization into the sphere stage; by contrast, maternal methylomes are reprogrammed such that their epigenetic states match the paternal methylomes after fertilization (Potok et al 2013;Jiang et al 2013). These findings suggest that the paternal DNA and maternal DNA undergo different dynamic changes.…”
Section: Introductionmentioning
confidence: 91%
“…5b). Recent research studying methylation in early zebrafish development using whole-genome bisulfite sequencing has revealed a cluster of differentially methylated regions (DMRs) that are hypermethylated in the egg, hypomethylated in the sperm, moderately methylated from the 2-cell to 256-cell stage, and hypomethylated at the sphere stage (Potok et al 2013;Jiang et al 2013). This cluster of loci has a relatively high CpG obs/exp ratio (~1.10) which is close to the obs/exp ratio (0.97) of the 4xUAS in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After fertilization, sperm DNA is quickly demethylated in mammals except in some specific loci (O'Doherty and McGettigan 2014;Miller et al 2010;Okada et al 2010) which are supposed to be necessary for a proper progress in early embryogenesis. However in zebrafish, whose sperm chromatin, as was explained before, is fully compacted with histones (Wu et al 2011), DNA reprogramming after fertilization follows a different mechanism, early embryos inheriting sperm DNA methylome (Jiang et al 2013). Maintenance of a proper methylation at specific gene promoters is required for an appropriate sperm function and aberrant methylation patterns have been associated with infertility and poor sperm quality in men (Jenkins and Carrell 2012b;Jenkins and Carrell 2012a;Houshdaran et al 2007).…”
Section: The Importance Of Chromatin Methylationmentioning
confidence: 99%
“…Remarkably, the methylation status of the maternally-derived genome was reset to the male pattern as one unit. 3 Of the large number of loci that were differentially methylated in the sperm and oocyte, most were resolved to the spermspecific pattern by gastrulation. Many of the loci that were differentially methylated encoded genes known to be involved in early embryogenesis, so this provides some reassurance that these reprogramming events are developmentally relevant.…”
mentioning
confidence: 99%